Awareness of Sexual and Reproductive Health among School-Going Adolescents in Selected Schools of Lalitpur District, Nepal - Adhikari, Anup; Aryal, Bhagwan; Khatiwada, Kamana; Khanal, Kalpana (International Research Journal of MMC, 2025)
Adolescence is a crucial development phase with several changes. It requires knowledge about sexual and reproductive health (SRH) to empower them with informed health choices to reduce unintended pregnancies and sexually transmitted infections. However, many of them lack accurate information, leading to confusion and misinformation. This study evaluates the impact of an educational intervention on SRH knowledge among 115 eighth and ninth-grade students in Lalitpur, Nepal. This ‘pre-post-test’ study assesses changes in knowledge regarding reproductive health, contraceptive methods, abortion, STIs, and menstruation before and after the intervention of an educational awareness package during 2023. A total of 25 multiple-choice test questions were administered to the students. Results indicate significant improvements across all domains: awareness of reproductive health increased from 13.9% to 36.5%, knowledge of contraceptive methods such as pills rose from 45.2% to 59.6%, and understanding of STIs surged from 34.8% to 75.7%. Additionally, misconceptions about menstruation decreased markedly. The mean knowledge score improved significantly from 8.18 (SD = 2.47) to 10.91 (SD = 2.78), with a p-value of 0.000 indicating statistical significance at the 1% level. These findings underscore the need for comprehensive school SRH education to equip adolescents with essential knowledge and skills, ultimately fostering healthier behaviors and reducing health risks within this vulnerable population. It highlights that while a one-time educational intervention can improve knowledge on SRH, the prevalence of certain misconceptions and knowledge gaps needs ongoing holistic education.